FACTORS CONTRIBUTING IN THE CHOICE OF WRITING STRATEGIES AMONG INDONESIAN EFL GRADUATE STUDENTS - Randy Listiyanto; Endang Fauziati; Slamet Supriyadi (ETERNAL (English Teaching Journal), 2020)
This study aims to describe the factors which contribute in the choice of writing strategies among Indonesian EFL graduate students. This study was conducted in Muhammadiyah University of Surakarta especially in the graduate program of English language studies. The subjects of this research are six students who enroll in the program. The instruments used for this research were questionnaire and interview. Afterwards, the data were analyzed by using Miles and Hubberman’s flow model. Based on the result of analysis, there is an arising finding that can be sketched out: factors contributing to the use of writing strategy were identified to be students’ belief, students’ awareness, students’ language proficiency, writing time, writing type, and writing activity environment. In conclusion, employing writing strategies in a high frequency by considering students’ belief, awareness, language proficiency, writing time, writing type, and writing activity environment is strongly essentials as it will help them to achieve a good writing outcome.